2012
DOI: 10.1111/j.1742-481x.2012.01082.x
|View full text |Cite
|
Sign up to set email alerts
|

Manuka honey‐impregnated dressings in the treatment of neuropathic diabetic foot ulcers

Abstract: In this study, we investigate the effect of manuka honey-impregnated dressings (MHID) on the healing of neuropathic diabetic foot ulcers (NDFU). A total of 63 Caucasians, type 2 diabetic patients followed up in the diabetic foot outpatient clinic comprised the study population. Patients were randomised in two groups as follows: group I patients were treated with MHID and group II patients were treated with conventional dressings (CD). The patients were followed up on a weekly basis for 16 weeks. Mean healing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
71
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(78 citation statements)
references
References 44 publications
2
71
0
5
Order By: Relevance
“…However, clinical treatments with compounds, such as cadexomer iodine and medical-grade honey, are usually administered for weeks, and the applications are repeatedly replaced with fresh dressings within the treatment period (85)(86)(87)(88). Consequently, while the effect may appear limited, this does not account for the repeated and lengthy exposure that would occur in clinical cases.…”
Section: Resultsmentioning
confidence: 99%
“…However, clinical treatments with compounds, such as cadexomer iodine and medical-grade honey, are usually administered for weeks, and the applications are repeatedly replaced with fresh dressings within the treatment period (85)(86)(87)(88). Consequently, while the effect may appear limited, this does not account for the repeated and lengthy exposure that would occur in clinical cases.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the potent activity of honey against antibiotic-resistant bacteria has further increased the interest for application of honey. Several honeys have been approved for clinical application [4][5][6]. A review of different antibacterial studies showed that the antibacterial properties of honey depend on the geographical origin of the honey [7] Honey bees has been traditionally recognized as valuable source of energy which contains antibacterial and antifungal proprieties [8].…”
Section: Introductionmentioning
confidence: 99%
“…Viscosity of local honey can fix sucking cups during applying them to skin surface. Honey has strong antibacterial and antibiotic effects that promote wound healing [113,114].…”
Section: Nbmentioning
confidence: 99%